Analisis Perbuatan Melawan Hukum dalam Perjanjian Konsesi Pelabuhan (Studi Kasus: Putusan Pengadilan Negeri Jakarta Utara Nomor 70/Pdt.G/2018/Pn.Jkt Utr) - Jeffry P Samosir (Universitas Negeri Surabaya, 2020)
Acts against the law have a wider scope than criminal acts. Provisions regarding acts against the law are regulated in Article 1365 of the Civil Code which states